2016
DOI: 10.1515/jhsl-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiality in Early Modern English Medical Treatises (1500–1700)

Abstract: This study investigates diachronic trends in the use of evidential markers in Early Modern English medical treatises (1500-1700), with data drawn from the Corpus of Early Modern English Medical Texts. The state of medical thought and practice in Early Modern England is discussed, with particular focus on the changing role that Scholasticism played during this period. The nature of evidentiality and types of scholastic vs. non-scholastic evidence are given attention, and quantitative results are outlined. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…That is, the discourse context in which references to the auctores occurs is one of disagreement and criticism, rather than of acceptance (Gloning 2011, 322-326;Whitt 2016). This is also clear in the present data set, as seen in (12) and (13): .…”
supporting
confidence: 62%
See 1 more Smart Citation
“…That is, the discourse context in which references to the auctores occurs is one of disagreement and criticism, rather than of acceptance (Gloning 2011, 322-326;Whitt 2016). This is also clear in the present data set, as seen in (12) and (13): .…”
supporting
confidence: 62%
“…Here, previous work on seem and scheinen (Aijmer 2009;Diewald & Smirnova 2010;Whitt 2015), perception verbs (Whitt 2010;Whitt 2017), and various adverbs (Biber & Finegan 1989;Downing 2001) provides useful guides as to which items serve evidential functions. On the other hand, recent "bottomup" analyses of evidentiality (Bednarek 2006;Gloning 2011;Grund 2012Grund , 2013Whitt 2016) It is acknowledged that there may be some overlap at certain period boundaries in the corpora: in English at 1700, for example, due to the presence of texts from 1700 in both EMEMT and ARCHER, and the fifty-year demarcations of the GerManC Corpus provide similar potential for overlap (although in practice this meant only a single text published in 1700 placed in the 1650-1700 rather than the 1700-1750 group). Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Evidentiality dominates in both genres and with both lockwords, and aside from an increase in the general use of epistemic stance markers, no diachronic trends could be found. Previous research on Early Modern English medical writing (Taavitsainen 2001(Taavitsainen , 2009(Taavitsainen , 2018Hiltunen & Tyrkkö 2009;Whitt 2016a) has uncovered diachronic developments regarding epistemicity during the period under investigation here. Perhaps by focusing only on specific forms, other forms of epistemic stance marking (particularly multi-word expressions) are missed (cf.…”
Section: Final Remarksmentioning
confidence: 95%
“…Contemporary notions of evidentiality(Aikhenvald 2004;Boye 2012;Whitt 2010Whitt , 2016a posit this as the speaker's (or writer's) source of information. This is naturally included in the current discussion, but so are cases where the source of knowledge may belong to a third party rather than the writer, as seen in example (3) with the woman 'who had a strong fancy'.…”
mentioning
confidence: 99%
“…Whitt (2011:347) offers the broader definition of the linguistic realization of a speaker or writer’s evidence for a particular proposition, focusing on the means of expressing evidentiality in ways other than grammatical encoding. Whitt (2016) studies the decrease in evidentials marking reported information sources, relative to direct perceptual and inferential evidence in Early Modern English medical texts. Chafe (1986), by contrast, defines English evidentiality as referring to modes of knowing and attitudes toward knowledge: this definition encompasses a range of lexical or grammatical phenomena such as modal verbs and adverbs (e.g., probably , certainly ) expressing induction and deduction, matrix clauses expressing belief ( I think , guess , etc.)…”
Section: Introductionmentioning
confidence: 99%